Exploratory Data Analysis: Visualization of Average Wages of Workers in Indonesia by Region of Residence using Google Data Studio - Wibowo, Gentur Wahyu Nyipto; Kraugusteeliana, Kraugusteeliana (PT.KARYA GEMAH RIPAH, 2024)
This study analyzes the average hourly wage of workers in Indonesia by region of residence, using data from the Central Bureau of Statistics (BPS) for the period 2018-2022. The data is divided into three categories: rural, urban, and combined urban and rural. The analysis was conducted using Exploratory Data Analysis (EDA) method and data visualization using Google Data Studio. The results of the analysis show that there is significant variation between wages in urban and rural areas. In rural areas, the highest average wage was recorded in 2020 at IDR 14,242, and the lowest in 2018 at IDR 11,557. Wages in rural areas increased from 2018 to 2020, then decreased in 2021 and 2022. In urban areas, the highest wage in 2021 reached IDR 20,234 per hour, while the lowest in 2018 was IDR 17,326 per hour. The wage trend in urban areas increased from 2018 to 2021, followed by a decline in 2022. The combined urban and rural data shows the highest wage in 2021 at 18,089 Rupiah per hour and the lowest in 2018 at 15,275 Rupiah per hour. The data visualization reveals that workers in urban areas have higher wages than workers in rural areas, with a five-year average of 28,957 Rupiah per hour in urban areas and 13,067 Rupiah per hour in rural areas. In conclusion, there is a significant disparity between wages in urban and rural areas, with a decline in wages by 2022 indicating an economic impact that requires adaptive policies.